The quality, safety and content of telephone and face-to-face consultations: a comparative study. Issue 4 (29th April 2010) - McKinstry, B; Hammersley, V; Burton, C; Pinnock, H; Elton, R; Dowell, J; Sawdon, N; Heaney, D; Elwyn, G; Sheikh, A
Abstract : Introduction: Telephone consulting is increasingly used to improve access to care and optimise resources for day-time work. However, there remains a debate about how such consultations differ from face-to-face consultations in terms of content quality and/or safety. To investigate this, a comparison of family doctors' telephone and face-to-face consultations was conducted. Methods: 106 audio-recordings (from 19 doctors in nine practices) of telephone and face-to-face consultations, stratified at doctor level, were compared using the Roter Interaction Analysis Scale (RIAS) (content measure), the OPTION (observing patient involvement in decision making scale) and a modified scale based on the Royal College of General Practitioners (RCGP) consultation assessment instrument (measuring quality and safety). Patient satisfaction and enablement were measured using validated instruments. The Roter Interaction Analysis Scale scores were compared by multiple linear regression adjusting for covariates; other continuous measures by χ 2 and Student t tests and binary measures as odds ratios. Results: Telephone consultations were shorter (4.6 vs 9.7 min, p<0.001), presented fewer problems (1.2 vs 1.8, p<0.001) and included less data gathering, counselling/advice and rapport building (all p<0.001) than face-to-face consultations. These differences remained significant when consultation length and number of problems were taken into account. Telephone consultations were judged less likely to include sufficient information to exclude important serious illnesses. Patient involvement and satisfaction outcomes were similar in both consultation types. Conclusion: Although telephone consultations are convenient and judged satisfactory by patients and doctors, they may compromise patient safety more than face-to-face consultations and further research is required to elucidate this. Telephone consultations may be more suited to follow-up and management of long-term conditions than for in-hours acute management.